MEMPREDIKASI TURNOVER INTENTION: PERAN GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN KOMPENSASI - Livani Yanuari; Didin Hikmah Perkasa; Magito Magito; Lingga Yuliana; Aditya Rian Ramadhan (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze and predict turnover intention, leadership style role, job satisfaction and employee compensation of manufacturing companies in Bekasi, West Java. This study uses primary data obtained through questionnaires that have been distributed directly through google forms to manufacturing employees. The population in this study is 344 manufacturing employees. Where the sample was taken using the slovin formula using the probability sampling method as many as 185 people. The data that has been obtained are processed with PLS-SEM to test the outer model, inner model and hypothesis test. The first stage is to compile a questionnaire with the basis of the dimensions and indicators of each variable studied. The second stage conducts testing for all research variables. The findings of this study show that leadership style has no influence on turnover intention, while job satisfaction and compensation have a negative influence on turnover intention